Chemical patterns of the TINRO Basin (Okhotsk Sea) in abnormally cold years - A. Р. Nedashkovsky; G. V. Khen; N. I. Savelieva (Известия ТИНРО, 2018)
Chemical parameters (dissolved oxygen content, concentrations of silicon, phosphate and nitrate, nitrate deficiency) in the TINRO Basin of the Okhotsk Sea (~1000 m depth) are considered for the years 2001–2002 with abnormally cold winters. The Basin water exchange with the southern Okhotsk Sea is limited by the threshold with 500 m depth. The warm Intermediate water penetrates to the Basin above the threshold only. The warm intermediate layer is rather thin (σθ = 26.88–26.92 or 400–500 m depth) in the years with abnormally cold winter. It is distinguished by high concentrations of nutrients and low oxygen content; moreover, their values are the highest/lowest for the entire Okhotsk Sea, presumably because of partial isolation of its water in the basin where it is captured by the water gyre and «aged» with biogeochemical processes. The deep waters of the TINRO Basin (σθ ~27.02) are formed by mixing of three components: intermediate Okhotsk Sea waters, waters of the temperature maximum layer and dense cold waters of the Shelikhov Bay. The portion of the latter water mass is evaluated as 37 %. It enriches the Deep water in the Basin with dissolved oxygen and provides relatively low concentrations of nutrients. The peculiarity of the TINRO Basin manifests in the fact that these processes in the deep-sea zone (800–1000 m) proceed with high velocities typical for shelf. In addition, in the deep waters of the Basin, there is a significant deficit of nitrate, presumably due to denitrification, which also proceeds with high rate. This suggests that non-conservative behavior of hydrochemical characteristics in the deep waters is caused by processes occurring on the surface of bottom sediments. The main reason for this behavior is probably an additional accumulation of biogenic material at the bottom of the TINRO Basin as the result of its transfer from shelf by the cold dense waters ventilating the Basin. The TINRO Basin, being a trap for the cold dense shelf waters, apparently is a convenient object for observing and analyzing climate change in the northeastern Okhotsk Sea.